Interplay of the drivers and deterrents of leisure counterfeit purchase intentions - Kos Koklic, Mateja; Vida, Irena (Journal of Business Economics and Management, 2016)
Drawing on complementary theoretical perspectives, in this study we empirically investigate the drivers and deterrents underlying the formation of attitudes to leisure counterfeits and purchase intentions, and examine rationalization as a moderator of the attitude-intention relationship. The research model is examined via mail survey data of adult consumers using structural equations modelling. The findings indicate that perceived benefits and moral intensity significantly influence attitudes, while the impact of performance risk is negligible. The attitude and moral intensity significantly predict the purchase intention. Our analyses confirm rationalization as a salient factor moderating the relationship between attitude and behavioral intention. Based on this pattern of results, we discuss study implications in three areas: the perception of positive consequences for oneself, the perception of consequences for others, and the use of previously rarely examined consumer justifications. The finding that performance risk is not significant in affecting consumer attitude calls into question various appeals featuring adverse effects of buying counterfeits for an individual.First published online: 29 Dec 2015